2021
DOI: 10.1021/acs.macromol.1c01464
|View full text |Cite
|
Sign up to set email alerts
|

Self-Exchange of Polyelectrolyte in Multilayers: Diffusion as a Function of Salt Concentration and Temperature

Abstract: Polymer chain diffusion within a hydrated polyelectrolyte complex, PEC, has been measured using an ultrathin film format prepared by the layer-by-layer method. Isotopically labeled self-exchange of deuterated poly(styrene sulfonate), dPSS, with undeuterated PSS of the same narrow molecular weight distribution permitted reliable estimates of whole-molecule diffusion coefficients, D . N a r r o w m o l e c u l a r w e i g h t d i s t r i b u t i o n p o l y -(diallyldimethylammonium), PDADMA, was used as the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Therefore, in our opinion, the main origin of the observed heating effect is interdiffusion and reorientation of polyelectrolyte molecules present at the multilayer–air interface. The diffusion process within the LbL assemblies was extensively studied for the past two decades by the Schlenoff group. They concluded that there are at least three types of diffusing species within PEM: ions, polymer chains, and extrinsic polyelectrolyte–counterion sites. We are convinced that in our experiments, the amount of energy that was brought to multilayer systems by heating was enough to overcome the energy barriers needed for the migration of all three diffusing species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in our opinion, the main origin of the observed heating effect is interdiffusion and reorientation of polyelectrolyte molecules present at the multilayer–air interface. The diffusion process within the LbL assemblies was extensively studied for the past two decades by the Schlenoff group. They concluded that there are at least three types of diffusing species within PEM: ions, polymer chains, and extrinsic polyelectrolyte–counterion sites. We are convinced that in our experiments, the amount of energy that was brought to multilayer systems by heating was enough to overcome the energy barriers needed for the migration of all three diffusing species.…”
Section: Discussionmentioning
confidence: 99%
“…Because polymer diffusion demands massive transport of a material, it is usually too slow to allow access of the polymer to an entire film (even at higher temperatures) . As a result, this migration of macroion chains takes place only in the interface region and thus causes morphological changes in the surface that were directly visualized here by AFM imaging (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyelectrolytes can be utilized through electrospinning, layer-by-layer assembly, solution complexation, and coacervate deposition. Polyelectrolyte deposition is well-known for its ambient processing, and utilization of environmentally benign materials in aqueous-based solutions, to generate functional thin films. There is little environmental concern in regard to these films due to lack of harmful solvents and materials that are often used to impart barrier properties on cellulosic substrates using more traditional approaches. Furthermore, these coatings are typically ionically cross-linked and can be expected to exhibit recyclable and self-healing behaviors due to the dynamic/reversible nature of ionic bonds. Coatings prepared with these charged polymers have been utilized for their flame retardant, dielectric, heat shielding, antifouling, and gas barrier properties. In the present study, the oxygen transmission rate (OTR) of polyethylenimine (PEI)-poly­(acrylic acid) [PAA] coacervates, prepared with and without clay nanoplatelets, on paper substrates is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have already been carried out to understand the kinetics of formation of these multilayers, the organization between the polymers or the ionic distribution within these multilayers [13,14,15,16,17,18]. However, to our knowledge, few studies have been performed on the possibility of using these multilayers to control the behavior of inorganic colloidal suspensions.…”
Section: Introductionmentioning
confidence: 99%